Psychoanalytic perspective of trauma in John Barth’s The Development: nine stories - Ghaderi, Ali; Taghizadeh, Ali (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
This study aims to investigate John Barth’s The Development in the light of trauma theory. Traumatic events were firstly discussed in Freud’s Studies in Hysteria, and then were revisited in Beyond the Pleasure Principle. They can have happened in the past life of a subject, can be unacceptable to their consciousness, and yet they can return in the form of compulsive and repetitive behaviors. Possible symptoms may be more the result of the subject’s repressed desires than traumatic events. Moreover, traumas are not only the result of the subject’s personal experience but the ramifications of the historical context and past environment to which the subject is bound. In Barth’s The Development: Nine Stories the tales are narrated by aging people who struggle with forces around them which affect their lives. These forces compel a couple to a pact of spontaneous suicide. Loss, family, and social dysfunction are among the other outcomes of trauma which are satirised in a conspiratorial tone. Symbolised in Heron Bay Estates, the American society is depicted as a gated community that must come to terms with the illusions of safety and conspiracy, for they are not walled off traumas that lurk in their most private moments. Barth demonstrates that a gated community can never protect its members from possible traumas. An analysis of traumatic experiences should be considered along with the linguistic and nonlinguistic means of representation through which an event is recollected because the event is reconstructed to reach equilibrium to comprehend the occurrence of the trauma. In the stories of The Development such verbal representations of temporality are enslaved to traumatic events. And this will explore how the narrative of a past history and temporality through traumatised subjects enable the representation of the hidden aspects both of history and the subconscious.